DAMPAK PEMBELAJARAN DARING TERHADAP PRESTASI AKADEMIK SISWA PASCA COVID-19 - Ramadhan, Hamdi; Oktavia, Annisa; Yunus, Syarifudin (Sindoro: Cendikia Pendidikan, 2025)
The COVID-19 pandemic has caused a shift in the education system from face-to-face learning to online learning. This study analyzes the impact of online learning on students' academic achievement after the pandemic by considering factors such as understanding the material, learning motivation, academic grades, effectiveness of learning media, and teacher support. Through a descriptive quantitative method involving 12 students of SMK Darur Roja Kholiliyah, it was found that 41.7% of students had difficulty understanding the material, and their learning motivation decreased. As many as 41.6% of students reported a decrease in academic grades, although 33.3% felt that online learning media were quite helpful. Teacher support had a positive effect on 75% of students, but social interaction was still less than optimal. Most students (41.7%) preferred face-to-face learning because it was considered more effective in improving academic achievement. The effectiveness of learning media and teacher support factors have a significant role in students' academic success. Therefore, innovative strategies are needed to improve the effectiveness of online learning to support students' academic achievement in the future. Pandemi COVID-19 telah menyebabkan pergeseran sistem pendidikan dari pembelajaran tatap muka ke pembelajaran daring. Penelitian ini menganalisis dampak pembelajaran daring terhadap prestasi akademik siswa pasca pandemi dengan mempertimbangkan faktor pemahaman materi, motivasi belajar, nilai akademik, efektivitas media pembelajaran, serta dukungan guru. Melalui metode kuantitatif deskriptif yang melibatkan 12 siswa SMK Darur Roja Kholiliyah, ditemukan bahwa 41,7% siswa mengalami kesulitan memahami materi, dan motivasi belajar mereka menurun. Sebanyak 41,6% siswa melaporkan penurunan nilai akademik, meskipun 33,3% merasa media pembelajaran daring cukup membantu. Dukungan guru berpengaruh positif bagi 75% siswa, namun interaksi sosial masih kurang optimal. Sebagian besar siswa (41,7%) lebih menyukai pembelajaran tatap muka karena dianggap lebih efektif dalam meningkatkan prestasi akademik. Faktor efektivitas media pembelajaran dan dukungan guru memiliki peran signifikan dalam keberhasilan akademik siswa. Oleh karena itu, diperlukan strategi inovatif untuk meningkatkan efektivitas pembelajaran daring guna mendukung prestasi akademik siswa di masa depan.